Pengembangan Pengembangan Media Big Book Pada Tema Cuaca Hujan Untuk Meningkatkan Literasi Membaca Siswa Kelas III Sekolah Dasar: Pengembangan Media Big Book Pada Tema Cuaca Hujan Untuk Meningkatkan Literasi Membaca Siswa Kelas III Sekolah Dasar - Bela, Nabila; Binti Mirnawati, Lilik; Setiawan, Fajar (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
The objective of this research is to create a product in the form of a Big Book that demonstrates quality in terms of validity, practicality, and effectiveness in improving the reading literacy of elementary school students at SDN Wonokusumo V. This research adopts a Research and Development (R&D) approach. In this study, the method utilized is the 4-D model of instructional development developed by Thiagarajan, consisting of four stages: Define, Design, Develop, and Disseminate. However, it is noteworthy that in this research, only the development stage is reached, and the dissemination stage is not implemented. Tests, the media development process, teacher and student response questionnaires, and expert validation are the tools used in this data collection method. The suitability of the instructional media is assessed based on: The Big Book has undergone a significant validation process, obtaining a validation percentage of 96% from media experts and 95% from material experts, both meeting the criteria of